Cross-cultural application of archetypal images in art therapy in China: A case study of Mandala images - Liu Yifei (SHS Web of Conferences)
Due to their ancient healing genes and significant modern therapeutic implications, Archetypal symbols have been widely employed in art therapy practices. However, research on their application effectiveness still lacks discussion in cross-cultural contexts. This study focuses on the use of archetypal symbols in art therapy—particularly Mandala images—within the cultural context of China. The research focuses on exploring the cultural adaptability of Mandala art therapy in China, along with the cultural challenges and opportunities faced in empirical studies. It further investigates the efforts made by Chinese therapists to optimize Mandala art therapy techniques, enabling better integration into Chinese cultural and therapeutic practices. The results indicate that although research and application in this field are still in the exploratory stage in China, Mandala drawing therapy has demonstrated effective healing and evaluative roles in empirical studies in China. It confronts cultural challenges with localized attempts, revealing the universality and localization trends of archetypal symbols in cross-cultural art therapy practices.